2016
DOI: 10.1039/c6sc02032a
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric-pressure ionization and fragmentation of peptides by solution-cathode glow discharge

Abstract: Ionization and tunable fragmentation of peptides at atmospheric pressure was achieved by means of a solution-cathode glow discharge ionization source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
1
23
1
Order By: Relevance
“…FAPA, or SCGD) can be tuned in 'hardness', enabling them to produce mainly molecular ions, fragment ions or atomic mass spectra, alternatively [150]. They are being evaluated at present to provide information about the amino-acid sequence of proteins and about the post-translational modification of proteins [151].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…FAPA, or SCGD) can be tuned in 'hardness', enabling them to produce mainly molecular ions, fragment ions or atomic mass spectra, alternatively [150]. They are being evaluated at present to provide information about the amino-acid sequence of proteins and about the post-translational modification of proteins [151].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Unlike the LS-APGD, no changes to the support solution composition were required to generate the biomolecular ions. Furthermore, the SCGD-MS results were significantly different from those obtained for biomolecular analysis with the LS-APGD [18,20]. Analysis of myoglobin by LS-APGD yielded an ESI-like charge-state distribution and no fragment ions, apart from loss of the heme group.…”
Section: Introductionmentioning
confidence: 58%
“…Earlier work with the SCGD as an ionization source for biomolecular mass spectrometry [20] revealed that fragmentation is tunable by adjustment of the discharge current. Similar results were observed here for small molecular species introduced within the liquid stream.…”
Section: Molecular Mass Spectra From Solutionsmentioning
confidence: 99%
See 2 more Smart Citations